Smart Contract Based Industrial Data Preservation on Block Chain - D.Sivaganesan (Journal of Ubiquitous Computing and Communication Technologies, 2020)
The ground work for establishing the industrial 4.0 age involves the tiered architectures that are made up of multiple planes encompassed with the physical things that are embedded with internet capabilities. This infrastructure enables an incorporation of the various functions that are necessary in a manufacturing industry to enhance the efficiency of the industry, and contrivance a highly supple and a self-organizing industry that is smart. On the other hand it becomes essential to preserve the information's safely as many internet enabled devices are utilized and more networks are formed for the proper incorporation of the various activities taking place. Since the conventional methods are inadequate the block chain method was most preferred due to its transparency and highly reliable and expedient services. To further structure a tamper proof network the blockchain is built with the smart contract laid on the system providing the impermeable authenticity on the industrial data transferred by securing the information's against the authentication that is anonymous. The performance of the system is validated to on the basis of security provided on the transactions made, and the cost spent on the proposed design
Keywords: Industry 40; Block Chain; Data Preservation; Smart Contract; Proof of Authenticity